The effect of stroke rate on activation patterns of rowing in boat and ergo meter trials: an EMG analysis - Sommer, M.; Schaar, H.; Mattes, K. (World Congress of Performance Analysis of Sport VIII, 2008)
Rowing cycle data were classified into drive and recovery phase and relative duration for both phases was calculated. For each stroke rate muscle onset was determined to analyse time points of muscle activation within the cycle. Percental duration of activity and time point of maximum amplitude was defined and compared for all intensities. All parameters were calculated for boat and ergo meter trials, respectively, with regard to evaluation firmness of rowing performance.